Analisis Tingkat Kesehatan Bank Bumn Di Daftar Bursa Efek Indonesia Dengan Metode Rgec (Risk Profile, Good Corporate Governance, Earnings, Capital) Periode 2021-2022 - Abd. Hafidh Ali; Arini Nur Fadilah (Mazinda : Jurnal Akuntansi, Keuangan, dan Bisnis, 2024)
A activities that requires its existence in the economic world is the business activities of banking financial institutions. The level of bank health is very important for the formation of trust in the banking industry. BUMN is the object of this research because BUMN Banks are the dominant business players in developing countries, including Indonesia. Seeing the very large role of state-owned banks in the Indonesian economy, it is hoped that state-owned banks will be able to compete by continuing to maintain their health so that they will have a positive influence on the national economy as a whole. The focus of the research is the health level of state-owned banks listed on the Indonesia Stock Exchange in 2021 and 2022 using the RGEC (Risk Profile, Good Corporate Governance, Earnings, Capital) method. The data used in this research is secondary data with data sources from the Indonesian Stock Exchange. The type of research used is non-experimental quantitative descriptive research. The data collection techniques used are documentation techniques and literature study. Rating the health level of state-owned banks using the Risk Profile, Good Corporate Governance, Earnings, Capital or (RGEC) method shows that the health ranking of BRI, BNI, BSI and Bank Mandiri in 2021-2022 is at Composite Rank 1 (PK-1) with the title "Very Healthy". State-owned banks during the 2021-2022 period are considered very capable of dealing with negative influences. Changes in business conditions and other external factors are reflected in the ranking of RGEC's assessment factors which are generally rated as very good. However, there are weaknesses, but in general these weaknesses are not significant and have a big impact. Risk profile factors reviewed with NPL and LDR indicators show that BSI has the title "very healthy" and is superior to Bank Mandiri, BNI and BRI. However, the assessment of the ROA, NIM and CAR indicators shows that BRI is superior to Bank Mandiri, BNI and BSI. In terms of GCG factors in 2021, Bank Mandiri is superior to others, while in 2022 Bank Mandiri and BSI have the title "very healthy" than BRI and BNI banks. The assessment of the health level in 2021-2022 reviewed using the RGEC method shows that BSI has the title "very healthy" compared to other state-owned banks